Pengembangan Umkm Berbasis Sumber Daya Kelautan: Pelatihan Abon Ikan Tuna Untuk Meningkatkan Pendapatan Pesisir Kelurahan Kambulabulana Kabupaten Buton - Muhammad Rais (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The objective of the community service program in Kambula-Bulana Village, Buton Regency, is to improve the skills and income of coastal communities through the production of tuna flakes using local resources. The main issues are that tuna catches are used to make byproducts, and there is a lack of community awareness regarding the production, processing, and distribution of MSME products. The methods used to implement this initiative include evaluating activity outcomes, providing guidance on product packaging, conducting outreach, and offering practical training in tuna flake production. The results of the community service program indicate that participants were able to understand the hygienic production process for tuna flakes and produce a product with higher value than fresh fish. Additionally, the community learned simple marketing techniques and attractive product packaging, thereby opening opportunities for the growth of home-based businesses in the fisheries sector. The skills, creativity, and economic potential of coastal towns have also increased thanks to this project.